2020
DOI: 10.3390/min10040383
|View full text |Cite
|
Sign up to set email alerts
|

Metasomatic Evolution of Coesite-Bearing Diamondiferous Eclogite from the Udachnaya Kimberlite

Abstract: A coesite-bearing diamondiferous eclogite from the Udachnaya kimberlite (Daldyn field, Siberian craton) has been studied to trace its complex evolution recorded in rock-forming and minor mineral constituents. The eclogite sample is composed of rock-forming omphacite (60 vol%), garnet (35 vol%) and quartz/coesite (5 vol%) and contains intergranular euhedral zoned olivine crystals, up to 200 µm long, coexisting with phlogopite, orthopyroxene, clinopyroxene (secondary), K-feldspar, plagioclase, spinel, sodalite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 122 publications
(216 reference statements)
0
12
0
Order By: Relevance
“…Hills & Haggerty, 1989) and (iii) the Siberian craton (e.g. Alifirova et al 2015; Mikhailenko et al 2020). In the following sections, we will discuss the possible implications of the presence of such UHP minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Hills & Haggerty, 1989) and (iii) the Siberian craton (e.g. Alifirova et al 2015; Mikhailenko et al 2020). In the following sections, we will discuss the possible implications of the presence of such UHP minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, oceanic crust is overlain by sediment and underlain by variably hydrated oceanic mantle, which dehydrate and partially melt at different P-T conditions (e.g., Schmidt & Poli 2014). The diverse liberated fluids and melts may then interact with the oceanic crust within paleo-subduction zones and leave characteristic signatures (Aulbach et al 2020) (see Section 5.2).…”
Section: Subduction Metamorphism (Eclogitization) and Interaction Wit...mentioning
confidence: 99%
“…Monocrystalline diamonds are xenocrysts (i.e., not genetically related) in kimberlite magmas (Richardson et al 1984) and occasionally found in situ in mantle xenoliths, including eclogite (e.g., Deines et al 1991, Ireland et al 1994, Viljoen 1995). These diamonds carry inclusions with mineralogies and compositions similar to those of their mantle source rocks (Meyer 1987). Due to the antiquity and chemical inertness of their diamond host, inclusions represent the early and deep record of the origin and evolution of eclogitic mantle sources and are therefore a complementary source of information to xenolithic eclogites (Stachel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The exceptionally fresh nature of xenoliths in the unserpentinized parts of the Udachnaya East kimberlite pipe has been highlighted (e.g., Ionov et al, 2010;Kamenetsky et al, 2012Kamenetsky et al, , 2014Kitayama et al, 2017). Unsurprisingly, eclogite xenoliths from that locality have been the focus of intense prior study, with interpretations converging on their origin as various parts of subducted oceanic crust (e.g., Agashev et al, 2018;Jacob et al, 1994;Jerde et al, 1993;Kolesnichenko et al, 2018;Mikhailenko et al, 2016Mikhailenko et al, , 2021Mikhailenko, Golovin, et al, 2020;Mikhailenko, Stagno, et al, 2020;Ponomarenko et al, 1980;Radu et al, 2017;Safronov et al, 1980;Snyder et al, 1997;Sobolev, 1977;Spetsius, 1995Spetsius, , 2004. Samples from the Udachnaya-East kimberlite in this study comprise 12 medium-to coarse-grained eclogite xenoliths.…”
Section: Geological Background Samples and Prior Workmentioning
confidence: 99%